Breaking The Shell of Candlenut Using Ripple Mill System with Various Immersion Temperature - Asrita Yohana Siallagan; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Generally candlenut are still broken traditionally. The product broken candlenut is affected by immersion process ofdrying and it will affect the product significantly. This research was performed in December 2011 up to February 2012 atAgricultural Engineering Laboratory, Faculty of Agriculture USU, Medan using non factorial randomized block design withone factor i.e immersion temperature (3 0C, 6 0C, and 9 C). The parameters observed were percentage of whole nut, thepercentage of nut broken in half, the percentage of crushed nut, the percentage of sticky core, immersion temperatureand engineering economics analysis using basic value, BEP, NPV, and IRR.  The results showed that immersiontemperature had significantly affected all parameters. The best result was immersion temperature at 3 0C. This equipmentis feasible to operate with the basic value of Rp. 119,92 kg-1, the BEP of 37.329,32 kg year, NPV of Rp. 8.121.452,19 ininterest 12% and Rp. 7.171.112,51 in interest 15%, and IRR of 37,64%.-10